Assessing the Interplay of Digital Literacy Skills and ICT Self-Efficacy in Enhancing Functional Skills: A Study at Islamic Secondary School Level in District Muzaffargarh, South Pakistan - Muhammad Kashif Majeed; Tunku Badariah Binti Tunku Ahmad (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to study the link between digital literacy competence and ICT self-confidence in enhancing functional competence among students of secondary school in the context of the Islamic secondary schools of District Muzaffargarh, South Pakistan. Since technology is being adopted in classrooms there is a need to understand the relationship between use of technology and students self efficacy on performance and skill acquisition ICT in particular. It is defined as the skill one require to have while Going For Information Using Technology To Obtain, Analyse and Disseminate Information. ICT self efficacy is defined as the extent of belief that one is capable of implementing applications of ICT. In the given context, the objective of the study is to assess the contemporary digital literacy tools with seminal emphasis on the presentation, assessment, and management of information within the context of teachers’ knowledge in these schools. Further, it investigates the extent to which it establishes the relationship between the modes of digital literacy competency and ICT self-confidence in the development of the functional skills like problem solving skills, critical thinking skills and description skills. Gender is also used to analyze knowledge and confidence of male and female students for using digital tools and ICT self efficacy. The present research therefore employs an exclusive quantitative research paradigm as it utilises questionnaires and statistical measures for the gathering and analyses of responses from students and teachers. It is expected that the outcomes set will enable the determination of the digital literacy and ICT self efficacy for improving function skills as well as educational attainment in secondary education.